Financial management practices: An in-depth study among the CEO of Small and Medium Enterprise (SMEs) - Mohd Harif, Mohd Amy Azhar; Osman, Harizal; Hoe, Chee Hee (World Business Institute, 2010)
The important contribution of small and medium-scaled enterprises in Malaysia’s GDP, employment, and industrialization has been well documented. Although their role in the economy is substantial, many SMEs are plaque by management problems (Hashim and Wafa, 2002).These management problems include human resource management, marketing management, operations management, financial management, and strategic management. Given that financial management is one of the key aspects of the well being and survival of a business, it is important that this topic is explored in depth. Thus, the main purpose of the present study is to investigate the financial management components and techniques practiced by the SMEs in Malaysia. The study comprises of two analyses, that is, in the first analysis, six financial management components were identified, namely financial planning and control, financial accounting, financial analysis, management accounting, capital budgeting, and working capital management. Subsequently, in the second analysis, various financial management techniques were identified under each component stated earlier.Data for the study is obtained by conducting a face-to-face interview using structured questionnaire with respondents from selected SMEs. The study sample comprised of 30 SMEs operating in the Kota Setar and Kubang Pasu district of Kedah Darul Aman.The findings of the study show that three components of financial management to be categorized as core components practiced by the SMEs, that is, financial planning and control, financial accounting, and working capital management.Three other components which are financial analysis, management accounting, and capital budgeting can be categorized as supplementary components practiced by the SMEs due to the small percentage of the SMEs using these components in the management of their business.